Profiles of 24-hour ambulatory blood pressure measurement and their association with cardiovascular risk factors in elderly high-risk hypertensive patients - Truong, Huy Hoang; Tran, Van Nam; Le, Thi Bich Thuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Hypertension is prevalent in the elderly, affecting two-thirds of individuals aged 60 years and older. Ambulatory blood pressure measurement (ABPM) is recommended for diagnosing and managing hypertension in this population. This study aimed to characterize 24-hour ABPM profiles and their association with cardiovascular risk factors in older adults with high-risk hypertension. Methods: A descriptive cross-sectional study included 96 patients aged ≥ 60 years, mean age 70.9 ± 7.9 years, 35.4% male (n = 34). Participants underwent routine clinical and laboratory assessments, including clinic and 24-hour ABPM. Pearson’s correlation coefficient was used to analyze the relationships between BP profiles and risk factors (p < 0.05). Results: Mean office systolic and diastolic blood pressure (BP) were 150.16 ± 26.06 mmHg and 81.46 ± 11.79 mmHg, respectively. Corresponding 24-hour ABPM values were 130.80 ± 17.43 mmHg and 73.73 ± 10.17 mmHg. The prevalence of masked uncontrolled hypertension was 12.5% (n = 12), morning surge was observed in 40.6% (n = 39), and 37.5% (n = 36) had isolated systolic hypertension. Nocturnal BP profiles were dipper [13.5% (n = 13), both systolic and diastolic], non-dipper [53.1%, (n = 51), systolic and/or diastolic], and riser [56.3% (n = 54), systolic and/or diastolic]. Mean 24-hour systolic BP correlated significantly with age (r = 0.229), body mass index (BMI) (r = 0.212), waist circumference (r = 0.226), creatinine level (r = 0.207), dyslipidemia (r = 0.223). Mean 24-hour diastolic BP significantly correlated with BMI (r = 0.294). Conclusion: Elderly high-risk hypertensive patients demonstrated a higher incidence of isolated systolic hypertension, morning surge, and non-dipping patterns. Mean 24-hour systolic and diastolic were significantly associated with cardiovascular risk factors. These findings emphasize the importance of comprehensive 24-hour BP monitoring in this population for better management and risk assessment